If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(3-x+3)=-18
We simplify the equation to the form, which is simple to understand
-7(3-x+3)=-18
Simplifying terms in parentheses
-7*(+6-1x)=-18
Reorder the terms in parentheses
+(-42+7x)=-18
Remove unnecessary parentheses
-42+7x=-18
We move all terms containing x to the left and all other terms to the right.
+7x=-18+42
We simplify left and right side of the equation.
+7x=+24
We divide both sides of the equation by 7 to get x.
x=3.42857142857
| 58q-2.8-5.2q=-0.4-2.2 | | 2x^2-24x+81=0 | | 14x^2+40x-6=0 | | x-7.6=-6.5 | | 12=-24y | | 4x+40=13x-68 | | r+33=14 | | -2t^2-6t+5=0 | | 5y-2+y+48=5y+50-1y | | 5x=165 | | 6x+34=14x+30 | | 3x+139=2x+26 | | y+25y-15y-9y=15-15 | | 2S=2Vt-gt^2 | | 5+x=(3+19x) | | 31+3x=34 | | 6x^2+4x=240 | | 9x+15-7x+15=-2 | | -113=5(5p+3)-3 | | s-44=-13 | | -4(x+5)+3=6(x+4)+1 | | f/2-19=-17 | | 8x-12=68 | | 6q=-6+7q | | 8x=6x+14 | | 5.85=0.65x | | -8=-(v+4) | | -7+6r=6r+3+r | | 8x-(x+3)(4x-5)=(5+2x)(4-x)-3(x+4) | | 6(8+3x)=174 | | 6y-25=4y+2 | | 17-9x=11+7x |